Peran Akuntansi Keperilakuan dalam Evaluasi Kebijakan Fiskal dan Efektivitas Pengelolaan Keuangan Publik - Dewa Dewa; Muh Erwinsyah; Ernawati Usman; Jurana Jurana; Mustamin Mustamin (Journal of State Economic Research, 2025)
Traditional fiscal policy relies on rational neoclassical models; however, reality demonstrates significant budget deviations stemming from individual cognitive limitations. This research addresses the urgent gap in applying behavioral theories within Public Financial Management. Using Systematic Literature Review and conceptual methods, the study synthesizes Behavioral Accounting, Public Administration, and Fiscal Economics from reputable secondary data. Results identify that cognitive biases, such as Overconfidence and Loss Aversion, inherently undermine budget credibility through unrealistic projections. This study formulates a Choice Architecture framework as an intervention tool to mitigate these biases in public financial reporting systems. Utilizing nudge strategies effectively enhances transparency, accountability, and fiscal compliance. Ultimately, integrating Behavioral Accounting into public standards and performance audits is crucial for ensuring rational, efficient, and transparent resource allocation to achieve high-quality national financial governance while fostering greater institutional trust through data-driven decision-making processes to stabilize the macroeconomy and enhance long-term public welfare outcomes for the state.